An investigation into the enzymatic activity of deepsea actinobacteria in decolourising crystal violet dye - Davids, Natasha (Centre for Bioprocess Engineering Research, 2020)
Crystal Violet (CV) decolourising deep-sea actinobacteria could provide a great source of novel redox biocatalysts that can be used in various applications such as removal of triphenylmethane dyes from contaminated wastewater and soil, degradation of aromatic environmental pollutants, biotransformation of antimicrobial agents and degradation of xenobiotics. CV is a triphenylmethane dye that has various applications, including use in medical, research and industrial applications, but its release into the environment poses a threat to aquatic life as it has characteristics of a biocide. Only a limited number of microorganisms are able to decolourise and degrade CV, and one of these proposed mechanisms by which they do so is the catalytic effect of oxidoreductase enzymes, including peroxidases, polyphenol oxidases and laccases. Triphenylmethane reductase has also been reported to be involved in decolourising CV, but the reaction involving this enzyme has not been studied systematically. Eleven deep-sea actinobacteria were investigated and found to decolourise CV by either biodegradation or biosorption. Gordonia sp. JC 51 was selected as a candidate for further study as it could decolourise CV efficiently and could tolerate high concentrations (1mM) of CV. A combination of spectral scan studies, dye decolourisation, biodegradation assays, enzymatic assays, SDS-PAGE, Native PAGE, TLC and LC/MS/MS methods revealed the mechanism involved in the decolourisation of CV. Gordonia sp. JC 51 decolourised CV via enzymatic and non-enzymatic mechanisms. However, true decolourisation of CV was performed via biodegrading enzymes. Triphenylmethane reductase and polyphenol oxidase was confirmed to be the enzymes involved. Leucocrystal Violet was identified as the metabolite produced. CV also was sequentially N-demethylated, oxidised and cleaved into smaller compounds such as Michler’s Ketone. In conclusion, Gordonia sp. JC 51 has potential as a whole cell biocatalyst and should be investigated further.